Analisis Break Even Point dan Margin Of Safety Sebagai Salah Satu Alat Perencanaan Laba pada Koffie 09 - Salma Benisha Amanda; Sihabudin; Robby Fauji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Profit planning is an important aspect for companies because it allows them to set profit targets to achieve in a certain period. This research aims to investigate the profit planning process, break-even point (BEP), and margin of safety (MOS) at Koffie 09 Karawang. The research method used is a descriptive approach with a quantitative approach. The data used is quantitative data from primary and secondary sources. Data collection techniques involve interviews and documentation. The results of this calculation provide an overview of the minimum sales point that needs to be achieved so that the company does not lose money, as well as providing guidance on the level of sales needed to achieve the set profit target. The findings from this research show that there are variations in achieving the breakeven point each year. In 2020 it was IDR. 575,942,010 or 30,989 Units. In 2021 it is IDR. 575,942,010 or 30,989 Units. In 2022 it will be IDR. 932,318,143 or 45,456 Units. Showing the safety of sales levels, 2020 has a margin of safety of 10%. In 2021 there is a margin of safety of 10%. In 2022 it has a margin of safety of 10%. Koffie 09 must sell 17,997 units or sales of IDR. 1,654,500,000 To achieve the profit planning goal in 2023, adjustments need to be made to the sales revenue target so that it does not cause losses for the company, which is 43.64% or IDR 722,181,857. It is hoped that the results of this research can help companies carry out optimal profit planning through BEP and MOS calculations.